Supplementary material 5. Dalyellia callvucurai. 3D representation of genital system from confocal image stack (PDF file) - Arias, Abril Agustina (2025)
Supplementary material 5. Dalyellia callvucurai. 3D representation of genital system from confocal image stack, (PDF file).